Impact of e-banking service quality on e-loyalty through interplay of e-satisfaction, an empirical evidence from commercial banks in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2023)
This research’s objective is to investigate how e-banking service quality influences customer satisfaction and how e-satisfaction impacts e-loyalty in Vietnam’s e-banking industry. Based on existing researches, the study creates a conceptual model that demonstrates the link between dependent and independent variables. Using a standardized questionnaire, 300 e-banking users from Vietnam provided the data. Using SPSS V26.0, descriptive statistics including reliability, and correlation analysis are calculated. AMOS V26.0 is then used to evaluate the impact of the mediator variable using confirmatory factor analysis. Results show that there is a positive relation between e-banking service quality and e-satisfaction and between e-satisfaction and e-loyalty. With a better understanding of the connections between service quality, customer satisfaction, and loyalty, particularly banks, may improve the quality of their services, which in turn increases customer satisfaction and loyalty.